طرائق تدبير كسور السنع الرابع و الخامس (كسر الملاكم) خبرة مشفى الأسد الجامعي بين عامي 2009-2010 - بطرس ميشيل; يوسف صفوان; سواري محمود (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة (66) مريضاً راجعوا مفشى الأسد الجامعي باللاذقية لديهم كسر في السنع الرابع أو الخامس(كسر الملاكم), وذلك في الفترة الواقعة مابين عامي(2009-2010). كان معدل إصابة الذكور أعلى بكثير من معدل إصابة الإناث (64ذكراً وَ2إناث) مع ذروة حدوث بعمر (30) سنة وإصابة اليد اليمنى أعلى بكثير من اليد اليسرى (64يد يمنى و2يد يسرى) . درست نتائج العلاج المحافظ وكانت نتائج العلاج الجراحي كما يأتي: عولج (46) مريض علاج محافظ بإجراء الرد بطريقة جاس((jhass مع وضع جبس لمدة أربعة إلى ستة أسابيع. وعولج(20) مريضاً علاجاً جراحياً :(21) مريضاً تم وضع أسياخ عبر الجلد بمساعدة التنظير الشعاعي, رد مفتوح وتثبيت بأسياخ عند(6) مرضى , ورد مفتوح و تثبيت بصفائح عند مريضين. مع تثبيت المعصم لمدة ثلاثة إلى أربعة أسابيع. كانت نتائج العلاج الجراحي أفضل بكثير مقارنة مع العلاج المحافظ من حيث فترة التثبيت و من حيث المضاعفات الحاصلة, حصل تبدل ثانوي عند (12) مريضاً من مرضى العلاج المحافظ تم إجراء الرد مرة أخرى عند(7) منهم في حين كانت المضاعفات عن مرضى العلاج الجراحي قليلة جدا This study includes (66) patients who visited the University Al-Assad Hospital in Latakia, with a fracture in the fourth or fifth metacarpals (Boxer’s Fractures), in the period between (2009-2010). The incidence rate of males was much higher than females (64 males and 2 females) with a peak incidence of 30-years age, and the injury of the right hand higher than the left hand (64 right hand and 2 left hands). Those results of conservative treatment and surgical treatment were examined as follows: (46) patients were treated by correction in a Jahss maneuver with a cast for four to six weeks. 20 patients were treated by Surgical treatment : 12 patients have been treated with percutaneous Kirscshner wires with assistance of radiography, open reduction and internal fixation with wires at 6 patients. Open reduction and internal fixation with plates in two patients. With the fixation of the wrist for a period of three to four weeks. The results of surgical treatment is much better compared with conservative treatment, in terms of the fixation period and complications occurring. There was a secondary displaced in 12 patients out of the patients with conservative treatment. The reduction was made again in 7 of them while the complications in the patients with surgical treatment were very few.